Application of the Healthy Eating Index in a multicultural population: introduction of Adaptive Component Scoring - Katz, David L.; Rhee, Lauren Q.; Aronson, Dina L. (Frontiers in Nutrition, 2025)
The United States, and many modern nations, represent assemblies of many cultural groups. Such groups are often influenced, sometimes profoundly, by the culinary traditions of their countries of origin, resulting in a diversity of cultural dietary patterns. Such patterns all derive key elements of nutritional quality from essential food groups—such as vegetables and fruits—but vary in their inclusion of “discretionary” food groups, such as dairy. The application of robust, validated, and standardized diet quality scoring is important in nutrition research, and in the food-as-medicine movement at large if what is being “managed” is to be measured. While robustly validated, the Healthy Eating Index is closely aligned with the Dietary Guidelines for Americans, and thus may not readily account for all multicultural dietary variations. Other diet quality metrics account for deviation from the prevailing American dietary pattern, but none does so in a way that expressly adapts to food components included or excluded so that “credit” for nutritional quality is appropriately assigned in all cases using a standard metric. In this context, we introduce and explain Adaptive Component Scoring as applied to the Healthy Eating Index in the service of advancing fair and universal diet quality scoring. Implications for nutrition research and food-as-medicine initiatives are briefly enumerated.